2009
DOI: 10.1111/j.1468-3083.2009.03224.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunocryosurgery for basal cell carcinoma: results of a pilot, prospective, open‐label study of cryosurgery during continued imiquimod application

Abstract: 'Immunocryosurgery' is a promising non-surgical combination modality to treat 'high-risk-for-recurrence BCCs'. Initial evidence is suggestive of an at least additive effect of the two combined modalities. Further studies comparing immunocryosurgery directly with cryosurgery and imiquimod monotherapies will confirm the reported results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 23 publications
1
35
0
1
Order By: Relevance
“…Immunocryosurgery was performed as described previously (11,16). Briefly, the patient was instructed to apply imiquitnod every night on each tumour and a skin zone of approximately 0.5 cm around the macroscopic tumour margins.…”
Section: Treatment Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunocryosurgery was performed as described previously (11,16). Briefly, the patient was instructed to apply imiquitnod every night on each tumour and a skin zone of approximately 0.5 cm around the macroscopic tumour margins.…”
Section: Treatment Protocolmentioning
confidence: 99%
“…We pioneered the combination of cryosurgery with topical imiquimod application (known as "immunocryosurgery") for the treatment of invasive BCC in an earlier pilot study (11). In addition, by modifying this method we have treated BCC cases that are difficult to treat with surgical removal (12), including periocular lesions (13), a localization where, according to some studies, Mohs surgery is associated with distinctly increased relapse rates (14).…”
mentioning
confidence: 98%
“…Patients should be warned that the warts can become quite painful during this treatment. Recent surveys have shown that combining imiquimod with cryosurgery seems to be more effective that either treatment alone in the treatment of skin cancer ("cryoimmunostimulation") [ 6 ]. Combination of imiquimod followed by cryosurgery is recommended when there are large and numerous genital warts.…”
Section: Anogenital Wartsmentioning
confidence: 99%
“…Yet topical imiquimod and cryosurgery combine additively in the framework of immunocryosurgery, as underlined by the substantially shorter freezing times employed in this approach (2,5). Notably, in selected cases where imiquimod alone elicits an inadequate inflammatory response (patient 1), this can be overcome by the addition of tazarotene.…”
Section: Sirsmentioning
confidence: 99%
“…Yet surgical treatment in challenging cases (large, multiple, confluent or recurrent BCCs) can be an arduous undertaking with relatively high relapse rates, particularly when conventional surgery is employed. 'Immunocryosurgery' has been recently introduced as a non-surgical, tissuesparing combination of cryosurgery during ongoing topical imiquimod for the treatment of 'nonsuperficial' BCCs (2).…”
Section: Sirsmentioning
confidence: 99%